Analysis of Workload and Needs for Nursing Staff at the Inpatient Installation of M.Zein Painan Regional Hospital - Hamrita, Dona; Firdawati, Firdawati; Arif, Yulastri (Newinera Publisher, 2025)
The nursing staff at M. Zein Painan Regional Hospital is experiencing an excess number of nurses which has a major impact on the hospital. Causing an increase in the burden of expenses and not having a function and maximum in improving the quality of service at the Hospital. The purpose of this study was to calculate the workload with the work sampling formula and calculate the need for nursing staff with the Ilyas method. This study was conducted starting in August 2024 using the mixed-methods method. The results of qualitative research showed that the nursing workload method system in the inpatient installation of M.Zein Painan Regional Hospital was not structured and the workload given to nurses did not match the number of nurses available. This is reinforced by the results of quantitative research on each inpatient installation at M.Zein Painan Regional Hospital with the Work Sampling method, the nurse's workload was relatively light. The number of nurses with the Ilyas Method found an excess of 43 nurses. The Hospital can carry out employee efficiency and effectiveness at M.Zein Painan Regional Hospital. It is hoped that this research can be the basis for a method for calculating the need for nursing staff at Class C Regional Hospitals.